A bibliometric analysis-based literature review of the relationship between sustainable water management and green innovations in the agricultural sector - Anita Boros; Bianka Gordos; Dávid Tőzsér (Heliyon, 2024)
Global water demand has grown intensively over the last three decades, and the predictions suggest this trend will continue. Sustainable Water Management (SWM) defines water-based principles and action frameworks interconnecting societal, economic, and environmental aspects to establish and maintain good practices serving long-term objectives related to water resources. Water scarcity, deterioration of water quality, less effective water technologies, hydrological changes caused by climate change, and increased water demand require the thorough revision of conventional approaches, new methods, and new policy measures. The research methodology in this paper includes a comprehensive review and bibliometric analysis of relevant literature on water management and sustainable development, including empirical studies, theoretical frameworks, and policy documents. The study explores the conceptual context of SWM, reveals the barriers hindering its core progress, evaluates the impact of green innovations on the development of novel operations, and gets an insight into the current policy and regulatory framework for SWM. Besides giving a review of the current practices and perspectives in SWM, the results of this study contribute to a deeper understanding of the complex relationship between sustainable water management and green innovations in the agricultural sector and provide possible directions toward adopting effective strategies and policies to promote a more intense permeation of the SWM approach.